Statins reduce dengue virus production via decreased virion assembly (2011)
Most of the effects of statins can be explained by pleiotropic effects independent of their lowering of serum cholesterol; in some cases, these effects have been shown to be a result of the role of statins in the prenylation of cellular proteins, some of which are involved in the life cycle of animal viruses. This study evaluated the potential antiviral activity of lovastatin (LOV) against dengue virus (DENV) infection of epithelial and endothelial cells (VERO cells, epithelial cells derived from African green monkey kidney, and HMEC-1 cells, human dermal microvascular endothelial cells). To evaluate its potential antiviral effects, LOV was used before, during and after inoculation of cell cultures with DENV. Before and after viral inoculation, LOV caused a reduction in virus yield (80% for HMECs and 25% for VERO cells). However, with LOV treatment after inoculation induced a marked increase (2- to 9-fold) in viral-positive RNA while the amount of viral protein increased only by 13-23%. A moderate reduction (1 log unit) in viral titer occurred concurrent with the increase in DENV genomic RNA and protein within the cells. According to our results, LOV appears to have a greater effect on viral assembly than on replication, resulting in the cellular presence of viral genomic RNA and proteins that fail to take the normal assembly pathway.